PROGRAM PSYCHOMOTOR THERAPY PERMAINAN KOORDINASI MATA-TANGAN UNTUK MENANGANI PERILAKU HAND FLAPPING ANAK AUTIS - RetnoTriswandari, - (2020)
It was motivated by the frequent emergence of hand flapping behavior of flapping/ wagging both hands simultaneously and repeatedly in children with autism during learning or playing. Verbal instructions given by the teacher are insufficient to raise children's awareness to stop doing hand flapping behavior. This study aimed to create and find out the extent of the psychomotor therapy program of eye-hand coordination games addressing the hand flapping behavior in children with autism. This study was conducted on MB subject, an autistic student of an SDLB. The result of this research was a psychomotor therapy program applied in the form of hand-eye coordination games, including hitting balloons, throwing and catching balls, throwing balls into containers, and throwing targets. The game served as a tool used to improve children's motor skills. Another result of this study indicated that children's motor skills improved and conversely, the intensity/ amount of hand flapping behavior decreased. This also answered the formulation of the problems proposed. The results of data processing and analysis on the balloon hitting game performed showed the mean level of the child's motor skills of baseline-1 phase (A-1) of 0%, intervention phase (B) of 33%, and baseline-2 phase (A- 2) of 75%. Data on the mean level showed an increase in the child's motor skills. Before being given the intervention, the child's motor movements were fixated on hand flapping behavior alone. After being given the intervention, the child was able to perform the task of hitting the balloon. Furthermore, data on the mean level of intensity/ amount of hand flapping behavior decreased in the baseline-1 phase (A-1) of 187 times, intervention phase (B) of 154, and baseline-2 phase (A-2) of 119 times. The change in score indicated a decrease in the number of hand flapping behavior of flapping/ wagging both hands simultaneously and repeatedly. Based on these results, it can be concluded that the psychomotor therapy program of eye-hand coordination games can address hand flapping behavior in children with autism in the MB subject. Keywords: Psychomotor Therapy, Hand Flapping Behavior, Children with Autism